2015
DOI: 10.1111/add.13052
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effect of a population‐based life‐style intervention on smoking and alcohol consumption. The Inter99 Study—a randomized controlled trial

Abstract: A population-based multi-factorial life-style intervention of 5 years' duration in Denmark had sustained beneficial effects on smoking abstinence and binge drinking 5 years after its discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…As depicted in Table 5, the multivariate analysis revealed that the number of HRFs was significantly increased in males (incident rate ratio, IRR = 1.18), [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year olds (IRR = 1.13), 50-64 year olds (IRR = 1.07), persons with the lowest (IRR = 1.39) or medium (IRR = 1.23) level of school education, and unemployed persons (IRR = 1.12).…”
Section: Multivariate Analysis On the Number Of Hrfsmentioning
confidence: 98%
See 1 more Smart Citation
“…As depicted in Table 5, the multivariate analysis revealed that the number of HRFs was significantly increased in males (incident rate ratio, IRR = 1.18), [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year olds (IRR = 1.13), 50-64 year olds (IRR = 1.07), persons with the lowest (IRR = 1.39) or medium (IRR = 1.23) level of school education, and unemployed persons (IRR = 1.12).…”
Section: Multivariate Analysis On the Number Of Hrfsmentioning
confidence: 98%
“…[19,39]). Encouraging findings on the efficacy of such interventions applied in the general population and general practice setting have been reported [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Worse, there are not enough resources and time to care for unhealthy behaviors, given that long-term multiprofessional intervention is required but is not provided. (9)…”
Section: Industrial Epidemics and The Livermentioning
confidence: 99%
“…Similarly, people attending cancer screening programs too rarely benefit from multidisciplinary lifestyle interventions by trained professionals to treat major obvious risk factors (smoking, alcohol use, obesity, physical inactivity, etc.) .…”
mentioning
confidence: 99%